Time-varying interactions between geopolitical risks and renewable energy consumption - Yifei Cai; Yanrui Wu (Asian Development Bank Institute (ADBI), 2020)
This study utilizes a time-varying parameter Bayesian vector autoregressive model to investigate the dynamic interactions between geopolitical risk (GPR) and renewable energy consumption growth (RECG). The identification strategy is flexible to accommodate cases both with and without sign restrictions. It is shown that GPR shocks have positive impacts on RECG over time. In contrast, RECG shocks decrease GPR in the whole sample period. These results show that renewable energy is a useful tool to reduce geopolitical risks. Meanwhile, the increasing geopolitical risks tend to augment renewable energy consumption. We also provide the responses at different time horizons and during particular geopolitical events. The estimating results are robust when industrial production growth is used as a control variable. Lastly, several implications for economic policy making are discussed.
Keywords: Q20; D80; C11; 330; renewable energy consumption; geopolitical risk; time-varying parameter VAR model; robustness checks